Peraturan Dalam Melakukan Pengisian Bahan Bakar Minyak Pada SPBU Berbasis Animasi 3D - Sumi Khairani; Nur Wulan; Bela Hafizil (SNASTIKOM, 2022)
Fuel Oil (BBM) is a commodity that plays a very important role in all economic activities, especially as a motorvehicle fuel. Along with technological developments in the automotive world, there is an increase in the numberof motorized vehicles every year. Indirectly there is an increase in the consumption of fuel oil. And from thisphenomenon there is an idea to educate the public about the regulations for refueling at gas stations using 3Danimation, to convey interesting information in such a way that the public and children can more easily understandthe regulations for refueling at gas stations. Starting from the ban on smoking or lighting a fire, using asmartphone, taking pictures in the filling dispenser area, the prohibition on starting the engine while still refueling,and compliance in the queue. In order to make gas stations more effective in conveying and implementingregulations for refueling at gas stations. The approach used is by making direct observations of the manual systemand recording carefully and systematically to collect data, in order to obtain the required information. As well asanalyzing the data and summarizing it so that it can draw conclusions that are used as benchmarks for making thesystem. And in making this 3D animation, several applications are used such as Blender, Hitfilm and Voicesove